Optimalisasi Peran Zakat untuk Pengembangan Kewirausahaan Umat Islam - Siti Najma (Sharia and Law Faculty, 2017)
Zakat is a social charity and humanitarian strategic and highly influential in the economic development of the people. One of the models is the innovative management of zakat productively, in which the method possible is to speed up efforts to alleviate poverty line, they are the ones mustahik initially and then into a muzakki. Zakat productive can be a source of funds for the development of entrepreneurial people. Entrepreneurship is expected to strengthen the economic and social level as well as the dignity of the nation, religion and civilization of Muslims. Stages that can be passed zakat institution in order to realize mustahik become a successful entrepreneur, including : (1) Economic incentives for the fulfillment of basic needs (basic needs) mustahik; (2) Education and training for entrepreneurship to provide entrepreneurial insights that can lead to motivation for entrepreneurship and also have entrepreneurial techniques in various aspects. (3) Business financing, in the form of qardhul hasan (4) The business partnership aims to strengthen the ability of small businesses to compete mustahik. Zakat institution can be a facilitator between mustahik and partners (5) Independence of the business, if the business has achieved independence, then the position mustahik has turned into muzakki.